A probabilistic verification algorithm against spoofing attacks on remote data storage. (2016) - Xu, Guangwei; Yang, Yanbin; Yan, Cairong; Gan, Yanglan
Remote data storage is a promising service and deployed in large-scale. The verification of data integrity is an important measure to protect the data from data corruption or loss in remote data storage environments. Current verification algorithms are mainly oriented to the service providers who may provide the false verification metadata or force the user to take fewer verification requests owing to the verification expense. To solve these issues, we propose a probabilistic verification algorithm to execute the routine verification and apply the homomorphism-based method to perform the challenge verification. The algorithm improves the metadata generation and innovates the metadata replacement to decrease the cost of verification and avoid the limitation of the traditional hash-based verification only executing for finite rounds. Theoretic analysis and simulation results demonstrate that our algorithm resists the spoofing attack as well as the excessive computation overhead at the expense of less cost in terms of verification data storage, transmission, and computation.